Experimental validation of finite element models representing stacked concrete beams with unbonded surface contacts. (15th January 2021) - Filippoupolitis, M.; Hopkins, C.
Highlights: FE modelling of the interaction between unbonded stacked reinforced concrete beams. Contact stiffness between concrete beams found to follow a lognormal distribution. Validation of finite element models carried out using experimental modal analysis. MAC and PMAC found to be of limited use when assessing the contact condition. Partial Modal Vector Ratio (PMVR) introduced as a supplement to MAC. Abstract: This paper investigates the dynamic behaviour of stacked reinforced concrete beams using experimental modal analysis and finite element methods. Finite element models of five different junctions were developed with surface-to-surface and edge-to-surface contact conditions between the beams. It was shown that the interaction between the beams could be approximated using a normal contact stiffness which is independent of the shape of the junction and follows a lognormal distribution. The models were experimentally validated in terms of eigenfrequencies and mode shapes. To assess the suitability of the model it was found to be essential to verify the spatial-average response. This was achieved by introducing the Partial Modal Vector Ratio (PMVR) as a supplement to the Modal Assurance Criterion (MAC) for the validation of the FEM models. PMVR is a time efficient approach to identify appropriate models and can be used as a supplementary criterion to MAC when there are correlation issues caused by the interaction of the beams.